A contribution to the knowledge of Quadraseta brasiliensis Goff and Gettinger, 1989 (Trombidiformes: Trombiculidae), with description of the deutonymph instar - Jacinavicius, F. C.; Bassini-Silva, R.; Mendoza-Roldan, J. A.; Muñoz-Leal, S.; Hingst-Zaher, E.; Ochoa, R.; Bauchan, G. R.; Barros-Battesti, D. M. [UNESP] (Les Amis d'Acarologia, 2018)
In the Neotropical region the genus Quadraseta Brennan, 1970, includes 14 species, with ectoparasitic habits during the larval stage. Quadraseta brasiliensis Goff and Gettinger, 1989, was described from larvae collected on the rodent Hylaeamys megacephalus (Fisher), cited as Oryzomys capito (Olfers). According to these authors, the holotype was deposited in the Museu de Zoologia da Universidade de São Paulo and the paratypes were deposited in three other collections: Bernice Pauahi Bishop Museum, Sam Noble Oklahoma Museum of Natural History and United States National Museum of Natural History, however, no type specimens were found in any of these museums. Here we redescribe the larva, describe the deutonymph instar obtained from field-collected larvae, and report new hosts and localities for this species in Brazil. In addition we provide sequences of the 18S ribosomal RNA gene for this species.
Keywords: Brazil; Chigger mites; Rearing; Small mammals